The Impact of 3D Printing Technology on the Accuracy and Efficiency of Dental Implant Placement: A Randomized Controlled Trial in Semarang, Indonesia - Reisha Notonegoro; Oliva Azalia Putri; Michelle Birne; Syaifudin Syaifudin; Indri Yani Septiana (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Accurate and efficient dental implant placement is crucial for successful treatment outcomes. Traditional implant placement techniques rely on 2D imaging and freehand surgery, which can be associated with inaccuracies and prolonged surgical time. This study aimed to evaluate the impact of 3D printing technology, specifically the use of patient-specific surgical guides, on the accuracy and efficiency of dental implant placement in Semarang, Indonesia. Methods: This randomized controlled trial included 60 patients requiring a single dental implant in the posterior mandible. Participants were randomly assigned to either the control group (conventional freehand implant placement) or the experimental group (3D printed surgical guide-assisted implant placement). Primary outcome measures were implant placement accuracy (deviation from planned implant position) and surgical time. Secondary outcomes included postoperative pain, swelling, and patient satisfaction. Results: The use of 3D printed surgical guides significantly improved implant placement accuracy in all three dimensions (mesiodistal, buccolingual, and apicocoronal) compared to the freehand technique (p<0.001). Surgical time was also significantly reduced in the experimental group (p=0.02). There were no significant differences between the groups in terms of postoperative pain, swelling, or patient satisfaction. Conclusion: 3D printing technology significantly enhances the accuracy and efficiency of dental implant placement. The use of patient-specific surgical guides resulted in more precise implant positioning and reduced surgical time, contributing to improved treatment outcomes.